A Study on Strategic Leadership of the Administrators for the Phrapariyattithamma Schools in Educational Division 11 for the Provinces of Sisaket, Nakhon Ratchasima, Chaiyaphum, Burirum and Surin - Meerakar, Amnuai (Academic MCU Buriram Journal, 2021)
The objectives of this research were to study and compare the study of strategic leadership for the administrators of Phrapariyattithamma Schools in educational division 11 for the provinces of Sisaket, Nakhon Ratchasima, Chaiyaphum, Burirum, and Surin by dividing on gender, age and working experience. The samples using for the research were 214 of Phrapariyattithamma Schools in educational Division 11 for the provinces of Sisaket, Nakhon Ratchasima, Chaiyaphum, Burirum, and Surin. The instruments using for the research were 5 rating scales questionnaires with the reliability of 0.92. The statistics using for data analysis included frequency percentage mean and standard deviation. The hypothesis testing included t-test (Independent Samples) and F - test (One – Way ANOVA) and the testing of couple variation by the regulation of Sheffe. The research result finds that: For overall on strategic leadership of the administrators and the teachers for Phrapariyattithamma Schools in educational Division 11 for the provinces of Sisaket, Nakhon Ratchasima, Chaiyaphum, Burirum, and Surin were in high level. The aspect with the highest level was revolutionary thinking. 2. Comparison on study for strategic leadership of the administrators of Phrapariyattithamma Schools in educational Division 11 for the provinces of Sisaket, Nakhon Ratchasima, Chaiyaphum, Burirum, and Surin, there were founded that the administrators and the teachers with different gender, age and working experience were not on difference.